2011
DOI: 10.1299/jsdd.5.523
|View full text |Cite
|
Sign up to set email alerts
|

Realization and Application of the Base Plate Jerk Feedback in a Pneumatic Positioning Stage

Abstract: In this paper a pneumatic positioning stage which is mounted on the base plate and supported by the coil-type spring isolators is considered. The stage is moved by the driving force during positioning and the reaction force causes vibration of the base plate with its natural frequency, which degrades the performance of the positioning. To reduce the effect of the reaction force and improve the positioning time, the base plate jerk feedback is proposed. An external force is used to realize the principle of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…In our preceding studies (8,9) , we showed that the BPJFB with positive polarity in a pneumatically actuated stage is the same as the base plate acceleration feedback with positive polarity in XY stages driven by the linear motors (10,11) . The only difference of these feedback controllers is based on the difference in the dynamics of actuation systems, which will be discussed later.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our preceding studies (8,9) , we showed that the BPJFB with positive polarity in a pneumatically actuated stage is the same as the base plate acceleration feedback with positive polarity in XY stages driven by the linear motors (10,11) . The only difference of these feedback controllers is based on the difference in the dynamics of actuation systems, which will be discussed later.…”
Section: Introductionmentioning
confidence: 83%
“…2. Where the mechanical system is modeled as a 2-DOF system due to the suspension of base plate on the coil-type spring isolators by neglecting the vertical motion (8)(9)(10)(11)(12) , for which the equations of motion are defined as follows:…”
Section: Proposed Control Block Diagram and Related Theorymentioning
confidence: 99%
“…For this reason, the BPAccFB has been proposed as a competent control scheme. However, in the case of pneumatic stages, to control the horizontal vibration due to the reaction force, the base plate jerk feedback is further efficient after the driving mechanism is formed as a perfect integrator (7) .…”
Section: A Review On Control Of the Flow Disturbance And Horizontal Vmentioning
confidence: 99%
“…Subsequently, we concerned the dynamic situation of the base plate by using the coiltype spring isolators as the supporting mechanism (7) . To suppress the flow disturbance, a simple pressure difference feedback was conventionally used along with a PI compensator in front of the pneumatic system, based on Ref.…”
Section: Application Of the Bpjfb And Pdd 2 Compensatormentioning
confidence: 99%
See 1 more Smart Citation